Unusual Gigantiform Angiomatosis of Jawbone. Issue 3 (14th May 2022) - Kumar, Niranjan; Anehosur, Venkatesh; Desai, Anil; Agrawal, Sayli; Prabhu, Avinash; Hallikeri, Kaveri
Abstract : Abstract: The purpose of this paper is to highlight rare highly infiltrative massive Angiomatosis and depict surgical outcome of a rare case series of gigantic lesions in the maxillofacial region. Data were recorded from the medical records of patients. Predictor variables were drawn from demographics, age, gender, site, evaluation of surgical treatment. The outcome variables were the challenges encountered and related complications. Out of 6 patients, the youngest was 10 and the oldest was 26 years old. Soft tissue and jawbone involvement were seen in 3 patients each with a single massive lesion involving both maxilla and mandible. All 6 patients had wide excision of the lesion with one patient having 2 stage procedures. No complications or recurrence was seen at 1-year follow-up. Angiomatosis is a rare and benign lesion in the head and neck region. its diffuse infiltrating nature may give a false malignant picture. it clinically mimics Hemangioma or Arteriovenous (AV) malformation thus requires thorough evaluation and its surgical intervention is challenging as described in this case series because of its magnitude and infiltrative nature.